Underwater Energy Harvesting and Sensing by Sweeping Out the Charges in an Electric Double Layer using an Oil Droplet. (27th January 2022) - Qin, Huaifang; Xu, Liang; Lin, Shiquan; Zhan, Fei; Dong, Kai; Han, Kai; Wang, Huamei; Feng, Yawei; Wang, Zhong Lin
Abstract: As an emerging technology for energy harvesting and distributed power supply, triboelectric nanogenerators are mainly based on a dielectric capacitive structure. Here, a new mechanism by introducing an oil phase into a water–solid interface is demonstrated for energy harvesting based on electric double layer (EDL) capacitance. Through squeezing and releasing oil droplets on a dielectric surface in water environment, charge transfer is observed in the back electrode accompanying the movement of the oil–water–solid three‐phase line. The charge transfer is mainly attributed to the effect that the oil phase sweeps away ions near the dielectric surface in the EDL due to the discrepancy of EDL between water–solid and oil–solid interfaces. Under the water environment, the device is shown to be capable of direct energy harvesting and self‐powered sensing without costly packaging. As a new working mode relying on EDL, it allows developing nanogenerators adaptive to severe environments even underwater with low friction and wear, and narrowing the gap between energy harvesting devices and electro‐chemical devices. Through further enhanced EDL, it is reasonable to anticipate devices with an ultrahigh charge density comparable with EDL super capacitors, opening up an avenue toward new nanogenerators with overwhelming performance for practical applications ranging from blue energy harvesting to electro‐catalysis. Abstract : A nanogenerator based on an electric double layer is realized by introducing an oil phase into a water–solid interface. Charge transfer is observed in the electrode accompanying the movement of the oil–water–solid three‐phase line. The device allows direct energy harvesting and self‐powered sensing underwater without packaging. It should also open up an avenue toward new nanogenerators with overwhelming performance based on electric double layers.